2015
DOI: 10.1080/10803548.2015.1029290
|View full text |Cite
|
Sign up to set email alerts
|

Preventive strength training improves working ergonomics during welding

Abstract: To investigate the effect of a preventive strength training program on cardiovascular, metabolic and muscular strains during welding. Welders are one of the occupation groups which typically have to work in extended forced postures which are known to be an important reason for musculoskeletal disorders. Subjects (exercise group) accomplished a 12-week strength training program, while another group served as controls (control group). Pre and post training examinations included the measurements of the one repeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
2
20
0
2
Order By: Relevance
“…A number of effects of PE have been reported, including decreased musculoskeletal symptoms and industrial accidents, reduced work injury-related expenditure, and fewer days of absence 6,[10][11][12][13][14][15][16] . However, the results of randomized controlled trials (RCTs) have shown no effect on the prevalence of low back pain or neck pain 17) ,n od ecrease in pain intensity 18) , and no prophylactic effects on musculoskeletal disorders 19,20) .…”
Section: Introductionmentioning
confidence: 99%
“…A number of effects of PE have been reported, including decreased musculoskeletal symptoms and industrial accidents, reduced work injury-related expenditure, and fewer days of absence 6,[10][11][12][13][14][15][16] . However, the results of randomized controlled trials (RCTs) have shown no effect on the prevalence of low back pain or neck pain 17) ,n od ecrease in pain intensity 18) , and no prophylactic effects on musculoskeletal disorders 19,20) .…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for these positions was that they are common from EFP in industrial workers and exert a maximum of physical effort as shown by our own group and others. 19,20 The task was to weld a fictitious seam of two metal-workpieces. In both positions, all participants welded one-handed with their dominant hand.…”
Section: Experimental Welding Taskmentioning
confidence: 99%
“…[13][14][15][16][17][18] Recently, our group evaluated the effect of a resistance training program. 19 In this pilot study, a 12-week resistance training program was able to reduce muscle stress response during welding task in novices. However, these results need to be confirmed in professional welders to derive specific training recommendations in terms of time, duration, and modality of exercise.…”
Section: Introductionmentioning
confidence: 96%
“…Welders comprise a large occupational group that works long hours in forced postures [1]. Maintaining forced posture can cause early muscle fatigue [2], while it can lead to work-related musculoskeletal disorders (WMSDs) in the long-term or in severe cases [3].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the Nordic Musculoskeletal Disorder Questionnaire, the results of ergonomics related to nurses have shown that poor working postures tend to cause WMSDs, and measures to prevent WMSDs in nurses have been proposed [9]. Other scholars have proposed starting from a training and management perspective to overcome or reduce the adverse effects of welding on the upper limbs by developing a training program for welders [1]. In addition, Francisco C and Edwin T analyzed the stress on the upper limbs during the work of the auto assembly welder.…”
Section: Introductionmentioning
confidence: 99%